Maternal and Neonatal Outcomes Post Bariatric Surgery: A Population-Based Study - Nader I. Al-Dewik (17039794) (2023)
Objectives  This study had two primary objectives. First, to evaluate the incidence, risk factors, and maternal and neonatal outcomes among pregnant women post-BS (the exposed group). Second, to evaluate these outcomes among pregnant women without a history of BS, these include women who are obese, overweight, and with normal weight (non-exposed groups). Design This population-based study was conducted using 12-month retrospective registry data from the PEARL-Peristat Study at the Women's Wellness and Research Center (WWRC) in Qatar. Methods: We examined 6,212 parturient women and their offspring. Participants were classified into exposed (post-BS) (N=315) and non-exposed (N=5897). Statistical analysis was conducted using SPSS 28 software. We analyzed the risk factors and outcomes using univariate and multivariable regression. Results were reported as odds ratios (cOR) and adjusted aOR with 95% confidence intervals (CI), while incidences were reported as percentages. P value was regarded as significant at <0.05 Results Qatari, advanced maternal age, Parity >1, diabetes, and hypertension were found to be significant risk factors for women with post-BS. In addition, women in the post-BS group were found to be significantly more likely to have a cesarean delivery (37.5% vs. 24%, aOR=1.59, CI 1.18-2.14), preterm babies (10% vs. 7%, aOR=1.66, CI 1.06-2.59), and stillbirth (1.6% vs. 0.4%, aOR=4.53, CI 1.33-15.50) compared to the normal weight women group. Moreover, post-BS women had a higher risk of low-birth-weight neonates than obese (15% vs. 8%, aOR= 1.77, CI 1.153-2.73), overweight (15% vs. 7%, aOR=1.63, CI:1.09-2.43), and normal weight (15% vs. 8%, aOR=1.838, CI 1.23-2.75) women. Finally, women in the post-BS group were more likely to have low-birth weight neonates (< 2500g) amongst term babies than obese (aOR= 2.19, CI 1.14-4.18) and overweight women (aOR= 1.84, CI 1.03-3.29). In contrast, post-BS had a lower risk of gestational diabetes than obese (19% vs. 40%, aOR=0.39, CI: 0.29-0.54) overweight (19% vs. 32%, aOR= 0.57, CI 0.42-0.79) women. Similarly, compared to the overweight group, post-BS had a lower incidence and risk of assisted birth (4% vs. 9%, aOR=0.46, CI 0.21-0.99). On the other hand, obesity significantly increased the risk of gestational diabetes, cesarean deliveries, and labor induction in comparison to the other groups. Conclusion  Pregnancies with post-BS should be considered a high-risk group for some outcomes and should be monitored closely. These findings may guide the future clinical decisions of antenatal and postnatal follow-up for post-BS women.